Interstitial deletion of 5q33.3q35.1 in a boy with severe mental retardation - Jin Hwan Lee; Hyo Jeong Kim; Jung Min Yoon; Eun Jung Cheon; Jae Woo Lim; Kyong Og Ko; Gyung Min Lee (Korean Pediatric Society, 2016)
Constitutional interstitial deletions of the long arm of chromosome 5 (5q) are quite rare, and the corresponding phenotype is not yet clearly delineated. Severe mental retardation has been described in most patients who present 5q deletions. Specifically, the interstitial deletion of chromosome 5q33.3q35.1, an extremely rare chromosomal aberration, is characterized by mental retardation, developmental delay, and facial dysmorphism. Although the severity of mental retardation varies across cases, it is the most common feature described in patients who present the 5q33.3q35.1 deletion. Here, we report a case of a de novo deletion of 5q33.3q35.1, 46,XY,del(5)(q33.3q35.1) in an 11-year-old boy with mental retardation; to the best of our knowledge this is the first case in Korea to be reported. He was diagnosed with severe mental retardation, developmental delay, facial dysmorphisms, dental anomalies, and epilepsy. Chromosomal microarray analysis using the comparative genomic hybridization array method revealed a 16-Mb-long deletion of 5q33. 3q35.1(156,409,412-172,584,708)x1. Understanding this deletion may help draw a rough phenotypic map of 5q and correlate the phenotypes with specific chromosomal regions. The 5q33.3q35.1 deletion is a rare condition; however, accurate diagnosis of the associated mental retardation is important to ensure proper genetic counseling and to guide patients as part of long-term management.